THE POLICY OF THE RUSSIAN EMPIRE ON LAND OWNERSHIP AND PROPERTY RELATIONS IN THE TURKESTAN REGION IN THE 60s–70s OF THE XIX Century (Based on the Activities of Official Authorities and Working Commission Representatives) - Usarov U. A. (TARIXIY TADQIQOTLAR, 2025)
This article explores the agrarian policy pursued by the Russian Empire in the Turkestan region during the early years of colonial rule, specifically in the 1860s– 1870s. It focuses on the Empire’s policy regarding land ownership and property relations in the region. The study analyzes the activities of official representatives of the imperial government and members of working commissions, who were tasked with developing the legal and regulatory framework for managing land ownership and property relations in Turkestan. The analysis is based on archival materials, contemporary sources, and scholarly research from different periods.